Principales complicaciones maternas y perinatales en gestantes adolescentes atendidas en el Hospital General Martin Icaza, noviembre 2023 – abril 2024. - Alcívar Sánchez, Daniel Alejandro (2024)
The objective of this work was: To identify the main maternal and perinatal complications in pregnant adolescents between 13 and 19 years of age treated at the Martin Icaza General Hospital, in the period of November 2023 - April 2024. Methodology: Quantitative, cross-sectional and retrospective approach study, with a sample of 225 women with maternal-perinatal complications, in which care from medical records belonging to the Martin Icaza General Hospital was used as an instrument. It is necessary to emphasize that understanding the causes and implications of maternal-perinatal complications is essential to provide better support to affected adolescents and to advance reproductive health care. Medical and emotional support can make a significant difference in the experience of those facing this situation, and public awareness of this issue is essential to ensure that those experiencing it receive the necessary support and care.